Dispute resolution mechanism for electricity supply industry in Nigeria - Raji, Barakat Adebisi; Jamiu, Toheeb Aremu; Tanimu, Adamu Idris (Penerbit Universiti Kebangsaan Malaysia, 2022)
Many Nigerian artisans have been rendered inactive in their various callings. One of the reasons for this is the poor supply of electricity by the designated industry. Unfortunately, many of these artisans do not know where to go and lodge their complaints when they are served expensive electricity bills. Therefore, this paper is aimed at evaluating the legal framework for electricity supply dispute resolution in Nigeria. It also examines the effectiveness of this legal framework. This paper employs a quantitative research approach by using a survey design for data collection and descriptive statistics for data analysis of the 15 stakeholders who were surveyed. The review showed that a dispute resolution outlet is provided for customers who may wish to express their complaints about easy access and quick settlements. The finding also revealed that the industry has moved to other more result-oriented dispute resolution mechanisms such as mediation, arbitration, and conciliation, among others. There is a regulatory commission charged with the dispensation of justice on dispute resolution. However, what is left is public enlightenment to enable people to explore these available dispute resolution outlets in order to minimize the settlement period.